2019
DOI: 10.15294/jpii.v8i4.19169
|View full text |Cite
|
Sign up to set email alerts
|

Active Learning Strategies in the Environmental Engineering Course: A Case Study at Curtin University Malaysia

Abstract: The current teaching approach of the undergraduate subjects is very dependent on conventional methods, without any participation and contribution of the students during the learning process. Active learning refers to any approach to instruction in which all students are required to involve in the learning process. The purpose of the manuscript is to evaluate the application of active learning in teaching the compulsory course in the environmental engineering department, Curtin University Malaysia. Green engine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…In addition, the "KI-coach" app provides opportunities for students to engage in authentic learning activities, which can be achieved using technology [95][96][97], such as planning their diet, monitoring their dietary intake, and tracking their physical performance. This dynamic learning environment facilitates the attainment of learning objectives and enhances student performance [98,99].…”
Section: The Impact Of Maai On Physical Education Undergraduates' Spo...mentioning
confidence: 99%
“…In addition, the "KI-coach" app provides opportunities for students to engage in authentic learning activities, which can be achieved using technology [95][96][97], such as planning their diet, monitoring their dietary intake, and tracking their physical performance. This dynamic learning environment facilitates the attainment of learning objectives and enhances student performance [98,99].…”
Section: The Impact Of Maai On Physical Education Undergraduates' Spo...mentioning
confidence: 99%
“…Several authors found that the conventional lecture approach is followed most of the time, leading to the low involvement of students [16]. People usually process the information they receive in different ways, so attention and focus can easily be lost, and participation in class activities can be missed [17,18]. To this end, alternative learning approaches have been proposed by researchers in this field, with active learning being one of the most popular methods.…”
Section: Learning Strategies In the Current Technical Landscapementioning
confidence: 99%
“…Good learning is learning that provides opportunities and love for students (Aesih, 2023). The learning process is able to motivate children's overall creativity, thereby making students active and learning enjoyable (Hadibarata et al, 2019). Students are directed to be active and participative during the learning process, so that learning is student centered and provide meaning for himself (Tegeh et al, 2021).…”
Section: Introductionmentioning
confidence: 99%